2018
DOI: 10.1016/j.pneurobio.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

And yet it moves : Recovery of volitional control after spinal cord injury

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 280 publications
(350 reference statements)
5
132
0
2
Order By: Relevance
“…Computational modeling and neurophysiological studies have shown that both TSS and invasive (e.g., epidural spinal stimulation) approaches primarily recruit dorsal root afferent fibers (Hofstoetter, Freundl, Binder, & Minassian, 2018; Ladenbauer, Minassian, Hofstoetter, Dimitrijevic, & Rattay, 2010; Milosevic, Masugi, Sasaki, Sayenko, & Nakazawa, 2019; Minassian et al, 2007; Sayenko et al, 2015). Additionally, many other neural structures can be directly impacted by the electrical field, including axons, synapses, neuronal cell bodies, and glial cells (Taccola, Sayenko, Gad, Gerasimenko, & Edgerton, 2018). As such, mechanisms of spinal neuromodulation may also include activation of spinal interneural networks and antidromic activation of ascending fibers in the dorsal columns.…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling and neurophysiological studies have shown that both TSS and invasive (e.g., epidural spinal stimulation) approaches primarily recruit dorsal root afferent fibers (Hofstoetter, Freundl, Binder, & Minassian, 2018; Ladenbauer, Minassian, Hofstoetter, Dimitrijevic, & Rattay, 2010; Milosevic, Masugi, Sasaki, Sayenko, & Nakazawa, 2019; Minassian et al, 2007; Sayenko et al, 2015). Additionally, many other neural structures can be directly impacted by the electrical field, including axons, synapses, neuronal cell bodies, and glial cells (Taccola, Sayenko, Gad, Gerasimenko, & Edgerton, 2018). As such, mechanisms of spinal neuromodulation may also include activation of spinal interneural networks and antidromic activation of ascending fibers in the dorsal columns.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of different animal models of spinal cord injury (SCI) have demonstrated that modulating the physiological states of spinal networks, pharmacologically and electrically and in combination with motor training enables improved motor performance (Edgerton et al, 2004;Ichiyama et al, 2005;Gerasimenko et al, 2008;Lavrov et al, 2008;Courtine et al, 2009;Harkema et al, 2011;Rossignol and Frigon, 2011;Gad et al, 2013a,b;Angeli et al, 2014;Capogrosso et al, 2016;Formento et al, 2018;Gill et al, 2018). Specific pharmacology methods including the use of quipazine (Quip) (Fong et al, 2005;Ichiyama et al, 2008b;Gad et al, 2015;Taccola et al, 2018) and strychnine (Strych) (de Leon et al, 1999;Gad et al, 2013bGad et al, , 2015 have been effective in activation in the locomotor spinal neural networks to enable locomotor activity in rodent with severe paralysis. Similar interventional approaches have been observed in humans with a severe spinal injury .…”
Section: Introductionmentioning
confidence: 99%
“…Plasticity in the operation of spinal neurons has been demonstrated within simple reflex pathways as well as in complex neuronal networks, e.g., those involved in locomotion, voluntary movements, or respiration (for references, see Fuller and Mitchell 2017, Rossignol et al 2008, Taccola et al 2018, and Wolpaw and Carp 2006. Changes have been also found in the excitability of nerve fibers (Jankowska 2017), the main issue of the present study.…”
Section: Introductionmentioning
confidence: 64%